2009
DOI: 10.1016/j.chemolab.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Blind decomposition of infrared spectra using flexible component analysis

Abstract: The paper presents flexible component analysis-based blind decomposition of the mixtures of Fourier transform of infrared spectral (FT-IR) data into pure components, wherein the number of mixtures is less than number of pure components. The novelty of the proposed approach to blind FT-IR spectra decomposition is in use of hierarchical or local alternating least square nonnegative matrix factorization (HALS NMF) method with smoothness and sparseness constraints simultaneously imposed on the pure components. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Moreover, as stated by the authors, the BTEM approach is inapplicable when the number of experimentally measured spectra is less than the number of observed components. Here, as well as in recent publications, [16][17][18] we have demonstrated that the sparseness-based approach successfully estimates pure components when the number of available mixtures is less than the unknown number of components.…”
Section: Setting Up An Experimentssupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, as stated by the authors, the BTEM approach is inapplicable when the number of experimentally measured spectra is less than the number of observed components. Here, as well as in recent publications, [16][17][18] we have demonstrated that the sparseness-based approach successfully estimates pure components when the number of available mixtures is less than the unknown number of components.…”
Section: Setting Up An Experimentssupporting
confidence: 75%
“…Thus, they are not applicable to the uBSS problem that is of central interest here. To estimate the number of analytes for an identified set of SAPs, we propose to use the clustering function: [16][17][18] ( ) ( )…”
Section: Data Clustering-based Estimation Of the Number Of Analytes Amentioning
confidence: 99%
“…Application of one or more a priori constraints (e.g., targeting a peak as in BTEM or overconstraining a fitting algorithm by using a fixed number of spectral components as in SOLD) can drive the estimation procedure. Blind decomposition methods, 55,56 if properly constrained, could also potentially be used to estimate bone spectra based on transcutaneous measurements. The results of this study demonstrate that the mineral/matrix ratio of cortical bone, which has frequently been used as a Raman-based indicator of bone health and strength, [4][5][6][7][8][9][10][11][12][13][14] can be measured transcutaneously by processing SORS data sets with SOLD ( Figs.…”
Section: Methodsmentioning
confidence: 99%
“…These are exactly two features of the results obtained from NMF. As a result, NMF has been applied to the data analysis of multicomponent spectra . However, in most of the related literatures involving NMF, the analyzed spectra are two dimensional.…”
Section: Introductionmentioning
confidence: 99%